Kelarutan Pigmen Anorganik Merah dan Biru Dalam Gelasi Mikroemulsi Water In Oil dari Sistem Air, (SDBS), dan Pentanol Untuk Tinta Ballpoint - Suci Liani Murni; Ali Amran (Departemen Kimia FMIPA UNP, 2021)
Research has been carried out on the solubility of red and blue inorganic pigments in water-in-water microemulsion gelation from water systems, (SDBS), and pentanol for ballpoint inks. The method used is the sol-gel method by changing the microemulsion liquid into a gel by the sol-gel process at low temperatures. The formation of gels from microemulsion water in oil is done by the addition of tetra ethyl ortho silicate and ethanol. The amount of tetra ethyl ortho silicate added was 1: 8 mole ratio to the amount of water in a microemulsion of water in oil. The purpose of this study is to prepare gel from microemulsion water in oil, and determine the stability of the ink obtained based on the solubility test, density and refractive index of inorganic pigments in red and blue so that it can be applied to ballpoint inks. The measurement of the refractive index is done using the ABBE Refractometer. The results showed that the gel produced was semi-solid and had the ability to dissolve inorganic pigments larger and obtain solubility results in red inorganic pigments by 0.087 grams while the solubility of blue pigments by 0.026 grams.